Does Standardization of Service Tax Volunteer and Location Affect on Taxpayer Satisfaction? - Deviana Sofyan Deviana; Dodi Agusra; Asepma Hygi Prihastuti (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2021)
This study aims to determine the effect of Tax Volunteer Service Standardization and Location on WPOP Satisfaction at the STIE Persada Bunda Tax Center. The variables used in this study consisted of independent variables, namely the Tax Volunteer Service Standard (X1) and Location (X2). The Tax Volunteer Service Standard (X1) uses the standards from the DJP Regional Office, including Service Management Standards, Human Resources Standards, Facility Standards, and Supervision Standards. The dependent variable in this study is Individual Taxpayer Satisfaction (Y). The number of samples in this study amounted to 100 respondents. The results of this study indicate that partially the service standard and location variables affect WPOP satisfaction. Meanwhile, simultaneously, the service standard and location variables have an effect on WPOP satisfaction.